Do mundo como norma ao lugar como forma: o uso do território pela estratégia da saúde da família - Aranha, Pablo Ruyz Madureira (2010)
This work aims to check whether there is a congruence between the purposes of regulations imposed by SIAB and the materiality constitution of places where your information is produced, since our hypothesis is that there is a mismatch between the rules and forms, which means, between reality as it is in places and how the territory is scrutinized by the Family Health Strategy (FHS) as for the performance of their teams as to the generation of their information. For this, the methodology used was the literature, documentary and empirical research, in special about territorialization of the Family Health strategy of Natal-RN. From the empirical mediation was possible to see the gap between full exploration and information produced by the ESF and the reality of the places. Thus, we highlight the importance of considering the conditioning of geographical forms as a guiding principle of the strategy for Family Health